Analyzing Teaching Needs to Develop Digital Technology Innovation for Learning Process during the COVID-19 Outbreak (Indonesian Journal of Curriculum and Educational Technology Studies, 2021)
This research examines the use of digital technology as an intervention plan for teaching during the COVID-19 outbreak in Indonesia. It assesses the readiness and preparedness of 103 social science lecturers from universities in Tangerang Kota to use digital technology for teaching during the pandemic. Many lecturers were reluctant to improve their abilities and skills in digital technology, and some found it challenging. The study used a quantitative and semi-structured qualitative method to analyze the application of technology and investigate lecturers' abilities and skills in using digital technology during the outbreak. The result revealed that 69 respondents were capable and skilled in developing technological innovation. The remaining 34 respondents faced difficulties and were advised to relearn the development of innovative technology for 21st-century learning. This research offers insights into the challenges and opportunities of using digital technology for teaching during a pandemic and highlights the importance of technological readiness. Abstrak Penelitian ini mengeksplorasi penggunaan teknologi digital sebagai rencana intervensi untuk mengajar selama pandemi COVID-19 di Indonesia. Penelitian ini menilai kesiapan dan persiapan 103 dosen ilmu sosial dari universitas di Tangerang Kota dalam menggunakan teknologi digital untuk mengajar selama pandemi. Banyak dosen yang enggan meningkatkan kemampuan dan keterampilan mereka dalam teknologi digital, dan beberapa dari mereka menganggapnya sulit. Studi ini menggunakan metode kuantitatif dan semi-terstruktur kualitatif untuk menganalisis penerapan teknologi dan menyelidiki kemampuan dan keterampilan dosen dalam menggunakan teknologi digital selama pandemi. Hasilnya menunjukkan bahwa 69 responden mampu dan terampil dalam mengembangkan inovasi teknologi. Sementara 34 responden lainnya mengalami kesulitan dan disarankan untuk mempelajari kembali pengembangan teknologi inovatif untuk pembelajaran abad ke-21. Penelitian ini memberikan wawasan tentang tantangan dan peluang penggunaan teknologi digital untuk mengajar selama pandemi serta menyoroti pentingnya kesiapan teknologi.